Determinan Audit Delay pada Perusahaan Pertambangan di Indonesia - Mellya Embun Baining; Beid Fitrianova Andriani; Nurbadaliah Ahmad (Indonesian Journal of Islamic Economics and Business, 2023)
This research was conducted to examine the effect of audit delay on mining the companies are consistently listed on the Indonesian Sharia Stock Index from 2015 to 2019. This study uses check delay as dependent variable while independent variables belong to the company size, complexity of company operation, audit fees, profitability and solvency. The sampling technique used is purposive sampling using 20 mining companies that meet the criteria with a research time of 5 years. The research method using panel data regression analysis with semi-log regression model with the dependent variable in the form of natural logarithms. The results of this study show that all independent variables affect audit delays at the same time. in mining companies in Indonesia.